2019
DOI: 10.1016/j.ijheatmasstransfer.2018.11.126
|View full text |Cite
|
Sign up to set email alerts
|

A permeable-membrane microchannel heat sink made by additive manufacturing

Abstract: Microchannel heat sinks are capable of removing dense heat loads from high-power electronic devices with low thermal resistance, but suffer from high pressure drops due to the small channel dimensions. Features that reduce the pressure drop, such as manifolds, increase fabrication complexity and are constrained by traditional subtractive manufacturing approaches. Additive manufacturing technologies offer improved design freedom and reduced geometric restrictions, expanding the types of features that can be pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…3-dimensional simulation models give an accurate result than 2-dimensional simulation models but computational time is less for a 2-dimensional model. Similar outcomes were found in the 2D and 3D simulation model studies conducted on the [29].…”
Section: Microchannel Heatsink (Mchs)supporting
confidence: 82%
See 2 more Smart Citations
“…3-dimensional simulation models give an accurate result than 2-dimensional simulation models but computational time is less for a 2-dimensional model. Similar outcomes were found in the 2D and 3D simulation model studies conducted on the [29].…”
Section: Microchannel Heatsink (Mchs)supporting
confidence: 82%
“…This study proved that the pressure drop in the sintered copper microchannel was higher than the microchannel machined conventionally and noticeably lower than the porous Copper microchannel fabricated by the Lost carbonate sintering method (LCS). Ivel L. Collins et al [29] performed the direct-metal-laser-sintering Schematic diagram of the transistor with liquid-cooled heatsink [21]. method (DMLS) for manufacturing of two MCHS models, PMM (permeable membrane MCHS) and MMC (manifold MCHS) heat-sinks shown in Figure 3.…”
Section: Microchannel Heatsink (Mchs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Syed-Khaja et al [ 14 ] used PBF to fabricate a heat sink design that showed key enabling advantages such as the reduction in volume, weight, and chip temperatures. To date, several other studies have emerged regarding heat sinks produced by additive manufacturing [ 5 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Collins et al (2019) [4] proposed and experimentally evaluated a novel permeable membrane microchannel (PMM) heat sink design. The AlSi10Mg aluminum alloy fabricated by DMLS was used to produce the features with complex and thin porous wall to overcome the pressure drop issues.…”
Section: Introductionmentioning
confidence: 99%